A Hover Fly, Allograpta obliqua (Say) (Insecta: Diptera: Syrphidae): EENY185/IN342, rev. 8/2004 - Weems, Howard V. (EDIS, 2004)
Revised! EENY-185, a 4-page fact sheet by H. V. Weems, is part of the Featured Creatures collection. Includes references. Published by the Entomology and Nematology Department, August 2004. EENY185/IN342: A Hover Fly, Allograpta obliqua (Say) (Insecta: Diptera: Syrphidae) (ufl.edu)